World Bank Research Digest, Vol. 13(1) - World Bank (World Bank, Washington, DC, 2019)
This issue focuses on Health and Nutrition and features the following articles: The Critical Role of Health and Nutrition in Supporting Development; The Income Losses from Childhood Stunting—and the Returns to Nutrition Programs Aimed at Reducing It; Measuring Physical Activity to Investigate the Link between Health and Productivity; Bed Nets and Politics in Tanzania; Investigating the Joint Effects of Parenting and Nutrition on Child Development; How Do Targeted Cash Transfers Affect Nutrition among Nonbeneficiary Children? Cities, Slums, and Child Nutrition in Bangladesh; The Dynamics of Child Development in a Very Low-Income Country; Can Offering People Gifts Increase Their Use of Health Services? Looking into the Black Box of Performance-Based Financing; The Importance of Good Roads in Access to Health Care; and Recent World Bank Research Publications on Health and Nutrition.